2006
DOI: 10.1016/s0022-5347(05)00166-7
|View full text |Cite
|
Sign up to set email alerts
|

The Tongue as an Alternative Donor Site for Graft Urethroplasty: A Pilot Study

Abstract: Harvesting the LMG is feasible and easy to perform. Compared with the buccal mucosal graft the LMG seems to be associated with less postoperative pain and a minor risk of donor site complications. These preliminary functional and esthetic data are satisfactory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
129
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(135 citation statements)
references
References 18 publications
4
129
1
1
Order By: Relevance
“…Simonato et al [33] First report on the use of tongue mucosa Figure 1: Histology of buccal mucosa [60] Figure 2: Microvasculature of buccal mucosa [60] …”
Section: Historical Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Simonato et al [33] First report on the use of tongue mucosa Figure 1: Histology of buccal mucosa [60] Figure 2: Microvasculature of buccal mucosa [60] …”
Section: Historical Perspectivementioning
confidence: 99%
“…[33] The lateral surface of the tongue offers a short mucosa, of about 7-8 cm long, and both lateral surfaces are available as donor sites if the need arises. [33] …”
Section: Tongue Mucosamentioning
confidence: 99%
“…(46) Among the good results of the oral mucosa urethroplasty, the lingual mucosa is no exception. In their pioneering report, Simonato et al (20) reported seven successful cases out of the 8 cases included in his study achieving a success rate of 87.5%. (20) In a following report, they reported a series of 29 patients with anterior urethral strictures who underwent urethral reconstruction using LMG.…”
Section: Results Of Oral Mucosa Urethroplastymentioning
confidence: 95%
“…(12)(13)(14)(15)(16)(17)(18)(19) Nowadays, buccal mucosa has become the mainstay of these tissue transfer techniques. (13) In February 2006, Simonato et al (20) described the results of the first pilot study on the use of the tongue as an alternative donor site for graft urethroplasty with good functional and aesthetic results. (20) One year later in a dog model, Song et al (21) investigated the feasibility of the LMG urethroplasty.…”
mentioning
confidence: 99%
See 1 more Smart Citation